2020
DOI: 10.17843/rpmesp.2020.374.6360
|View full text |Cite
|
Sign up to set email alerts
|

Trastornos del sueño a consecuencia de la pandemia por COVID-19

Abstract: Las complicaciones respiratorias por la COVID-19 pueden llevar a la muerte, por lo que, dentro de las políticas de protección para evitar los contagios masivos, se han sugerido estrategias de cuarentena y confinamiento en muchos países, que han originado alteraciones en la salud mental y el sueño. A través de la siguiente revisión narrativa se pretende sistematizar los hallazgos más significativos en cuanto a la presencia de insomnio en pacientes hospitalizados con COVID-19, y de personas sanas que han estado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
(37 reference statements)
0
12
0
7
Order By: Relevance
“…For healthy people in quarantine, lifestyle changes, fear of infection, and reduced ability to cope with stress contribute to insomnia. 23 Psychosocial and mental stress can also affect sleep patterns and lead to a worsening of individual sleep quality. 24 A paper reported that the COVID-19 pandemic will affect circadian rhythms, leading to sleep-wake disturbances.…”
Section: Covid-19 Pandemic and Sleep Disordersmentioning
confidence: 99%
“…For healthy people in quarantine, lifestyle changes, fear of infection, and reduced ability to cope with stress contribute to insomnia. 23 Psychosocial and mental stress can also affect sleep patterns and lead to a worsening of individual sleep quality. 24 A paper reported that the COVID-19 pandemic will affect circadian rhythms, leading to sleep-wake disturbances.…”
Section: Covid-19 Pandemic and Sleep Disordersmentioning
confidence: 99%
“… El 43,5% de los encuestados informó la aparición de problemas de sueño y un 48% el empeoramiento de trastornos previos. Medina O, et al 35 Perú 2020 Artículo de revisión de 12 estudios. El insomnio en tiempos de pandemia se asocia con el sexo femenino, jóvenes y personas con antecedentes psiquiátricos, siendo influenciada por su enfrentamiento al estrés, ansiedad y estilos de vida.…”
Section: Insomnio Y Pandemia Covid-19unclassified
“…Thirty-six percent of the sample reported general and psychological discomfort; 42 % mentioned irritability and moodiness; 45 % reported sleep problems; 53 % expressed the need for psychological help to address stress and anxiety problems; 12 % showed depression and 65 % stated that they had food problems (15). Thus, the various situations caused by the pandemic have led to depression, stress, anxiety, anguish, and even panic worldwide (16), which has been widely documented in scientific literature, stating that the consequences of the pandemic are not only economic, social and medical but also of a psychological nature due to its serious consequences on mental health (17).…”
Section: Introductionmentioning
confidence: 99%